Oral history interview with Albert W. Tucker - Tucker, Albert W. (Albert William), 1905- (Charles Babbage Institute, 1986)
Tucker, a professor of mathematics at Princeton University from the 1930s until the 1970s, describes mathematics in Princeton in the late 1930s and during the years of the second world war. Topics include: personnel and personnel changes at the Princeton University Mathematics Department and the Institute for Advanced Study School of Mathematics; Solomon Lefschetz as the leader of the mathematical research program in the university; the later careers of James Alexander and Oswald Veblen; active mathematical research areas in Princeton; the move of the Institute for Advanced Study to Fuld Hall in 1939; the impact of the physical separation of the Institute and the University mathematics programs; teaching of mathematics to military personnel during the war; and mathematical contributions to the Fire Control Project located in Princeton during the war and to war-time calculation. Tucker also recounts his own career during this period, including his research, his war-time teaching of mathematics and use of the slide rule, and his suggestions for improvements in calculating aids for the military.
Transcript, 38 pp.
Keywords: Computer history; Princeton University. -- Dept. of Mathematics; Mathematics -- United States -- Study and teaching (Higher); Mathematics -- United States -- Research; Mathematicians -- United States; Lefschetz, Solomon, 1884-1972; Institute for Advanced Study (Princeton, N.J.). -- School of Mathematics; Alexander, James W. (James Waddell), 1888-1971; Veblen, Oswald, 1880-1960